Epidemiological and operational overview of piauí state tuberculosis: a portrait of a decade (Research, Society and Development, 2020)
Tuberculosis (TB) is an infectious disease transmitted by Mycobacterium tuberculosis. It is characterized as an emerging and global health problem. To evaluate the epidemiological and operational aspects of notified TB cases in the state of Piauí. This was a documentary, retrospective, descriptive research with a quantitative approach. Data were collected from the Department of Informatics of the Unified Health System (DATASUS) having as variables studied: year of diagnosis, incidence, mortality, type of entry, clinical form, laboratory confirmation, Directly Observed Treatment (DOT) performed, and situation of closure. We studied 10,956 cases of TB and, through these cases, it was observed that over the years there was a decline in the number of reported cases. The state has the average annual incidence and mortality rate, respectively, 29.5 cases / 100 thousand inhabitants and 2 deaths / 100 thousand inhabitants. It was observed that the type of entry per new case (85.3%) and the pulmonary form of the disease (83.4%) prevailed. Laboratory confirmation was performed in 60% of cases and DOT in 55.4% of cases. Regarding the evolution of cases, cure was the main outcome (69.4%). The investigation made it possible to know the characteristics of tuberculosis in the studied population, where it was observed that, over the years, there was a reduction in the number of reported cases, a recent increase in incidence and mortality, most of them are new cases, with pulmonary form. with the diagnosis by laboratory confirmation, with the DOT performed and progressing to cure.